2016
DOI: 10.1007/s11999-015-4650-x
|View full text |Cite
|
Sign up to set email alerts
|

Smoking is Associated with Increased Blood Loss and Transfusion Use After Lumbar Spinal Surgery

Abstract: Background Little is known about the association between smoking and intraoperative blood loss and perioperative transfusion use in patients undergoing spinal surgery. However, we found that although many of the common complications and deleterious effects of smoking on surgical patients had been well documented, the aspect of blood loss seemingly had been overlooked despite data reported in nonorthopaedic sources to suggest a possible connection. Questions/Purposes We asked: (1) Is smoking associated with inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(24 citation statements)
references
References 49 publications
1
23
0
Order By: Relevance
“…Our results further showed reduced intraoperative blood loss among active smokers, which is in contrast to the findings of previous studies: McCunniff et al . report a linear correlation between packs smoked per day and estimated intraoperative blood loss, with an additional blood loss of 330 mL per pack smoked. It is unclear whether the significantly younger age of our smoking patients had a confounding influence on these results.…”
Section: Discussionsupporting
confidence: 51%
See 1 more Smart Citation
“…Our results further showed reduced intraoperative blood loss among active smokers, which is in contrast to the findings of previous studies: McCunniff et al . report a linear correlation between packs smoked per day and estimated intraoperative blood loss, with an additional blood loss of 330 mL per pack smoked. It is unclear whether the significantly younger age of our smoking patients had a confounding influence on these results.…”
Section: Discussionsupporting
confidence: 51%
“…Whereas complex multi‐level spinal surgeries or open surgeries were observed to carry higher complication risks in elderly patients, this did not hold true among elderly patients undergoing MIS. In view of these findings, it is reasonable to assume that MIS provides a promising and innovative alternative for elderly patients, but also for patients with significant co‐morbidities, and other risk factors, such as obesity and active smoking status. The number of obese patients is increasing due to changed lifestyles, and body mass index impacts surgical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The subgroup analysis of the microdiscectomy and decompression patient cohort demonstrated a significantly greater mean ODI score in those that currently smoke. Recent literature has demonstrated increased complication rates in smokers [ 15 ], so this adds further evidence to the importance of counselling smokers with regard to cessation prior to their procedure as this could also impact the long-term outcomes after their operation.…”
Section: Discussionmentioning
confidence: 98%
“…38,39 Conversely, Grosflam et al found no association between smoking and blood transfusion requirements in primary THA, while McCunniff et al found that smoking increased the risk of transfusion after lumbar spine surgery. 40,41 These conflicting findings are likely explained by the fact that while smokers tend to have higher baseline hemoglobin levels, 42 they may also have an increased risk of bleeding through impairment of platelet membrane function and alterations in the clotting cascade. [43][44][45][46] Irrespective of the effect of smoking on anemia, surgeons should counsel their patients on smoking cessation prior to elective rTHA to minimize risks of infection and wound complications.…”
Section: Discussionmentioning
confidence: 99%